Pengaruh Promosi Melalui Media Sosial Dan Word Of Mouth Terhadap Keputusan Konsumen Memilih Wedding Organizer (Studi Pada Konsumen Art Project Lampung di Kecamatan Trimurjo Lampung Tengah) - Karnila Ali (Jurnal Manajemen dan Bisnis (JMB), 2020)
AbstractThis type of research is quantitative and in this study uses descriptive analysis. Method to collect data in the field is by taking a sample of a population of 60 respondents in Lampung Art Project consumers. The requirements analysis test uses normality test, linearity test and homogeneity test. Testing the analysis model using multiple regression, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R2), and statistical hypothesis test. Based on the results of research with multiple linear regression analysis with t-test obtained promotion  through  social  media  has  a  positive  and  significant  effect  on consumers’ decision to choose a wedding organizer, while word of mouth has a positive and not significant effect on consumers' decision to choose a wedding organizer. From the F-test obtained promotion through social media and word of mouth simultaneously give significant influence on the decision of consumers to choose a wedding organizer.Keywords : Promotion through Social Media, Word of Mouth, Consumer Decisions